2023
DOI: 10.3389/fbioe.2023.1126737
|View full text |Cite
|
Sign up to set email alerts
|

Biological treatment of biowaste as an innovative source of CO—The role of composting process

Abstract: Carbon monoxide (CO) is an essential “building block” for producing everyday chemicals on industrial scale. Carbon monoxide can also be generated though a lesser-known and sometimes forgotten biorenewable pathways that could be explored to advance biobased production from large and more sustainable sources such as bio-waste treatment. Organic matter decomposition can generate carbon monoxide both under aerobic and anaerobic conditions. While anaerobic carbon monoxide generation is relatively well understood, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 116 publications
0
3
1
Order By: Relevance
“…In this study, significant changes in CO emissions were observed; meanwhile, in other research, average CO emissions did not statistically differ between 3% biochar and control piles [62]. Hellebrand and Schade demonstrated that the CO produced during composting is generated by abiotic reactions and not by microorganisms [64], but our own research shows that CO emissions differ in biotic and abiotic conditions [63], and there are a lot of different pathways when CO can be generated during the composting by microorganisms [65]. As biochar can positively affect the microbial community-the population of actinomycetes, cellulolytic and proteolytic bacteria showed increases over the period of composting [66]-this effect should be examined in future studies.…”
Section: Co Emissionscontrasting
confidence: 58%
“…In this study, significant changes in CO emissions were observed; meanwhile, in other research, average CO emissions did not statistically differ between 3% biochar and control piles [62]. Hellebrand and Schade demonstrated that the CO produced during composting is generated by abiotic reactions and not by microorganisms [64], but our own research shows that CO emissions differ in biotic and abiotic conditions [63], and there are a lot of different pathways when CO can be generated during the composting by microorganisms [65]. As biochar can positively affect the microbial community-the population of actinomycetes, cellulolytic and proteolytic bacteria showed increases over the period of composting [66]-this effect should be examined in future studies.…”
Section: Co Emissionscontrasting
confidence: 58%
“…As substrates rich in organic carbon, they are currently mainly subjected to composting or anaerobic digestion processes; however, their potential is constantly recognized in other areas, such as biorefinery processes [ 1 ]. Despite the development of this field of study in recent years, so far, the possibility of coupling “conventional” waste-processing processes with the production of valuable biochemicals or biofuels by converting generated process gases has not been taken into account [ 2 ]. However, the bio-waste composting process, during which net carbon monoxide (CO) production has been observed, has the potential to couple these processes [ 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing these challenges, China has outlined goals for agricultural sustainability to ensure the comprehensive utilization of livestock waste and crop straw by 2030 [9][10][11]. Given the urgency of harmless manure treatment, composting-a widely used method-transforms livestock and poultry manure into organic fertilizer, increasing agricultural yield and mitigating soil degradation from traditional fertilizers [12][13][14][15][16]. However, uncontrolled factors such as temperature, humidity, and ventilation during natural fermentation composting can lead to incomplete decomposition, resulting in wasted resources, environmental pollution, and ineffective composting [17][18][19].…”
Section: Introductionmentioning
confidence: 99%